Structural and Photophysical Investigation of Lanthanoid Complexes of Calixarene-Based Antenna Ligands - Shen, Chao (Curtin University, 2021)
This thesis presents investigations into structural and photophysical properties of naphthalenetetracarboxylic diimide (NDI) functionalised calixarenes and their corresponding lanthanoid complexes. Six new calixarene ligands were synthesied and fully characterised. Upon complexation, europium (III), ytterbium(III) and neodynium(III) luminescence can be induced by energy transfer from the NDI of ligand and/or calixarene aromatic backbone. The reduction of neutral NDI to NDI radical anion was successful, and the NDI radical anion also sensitised ytterbium(III) luminescence.